2013
DOI: 10.1016/j.cmet.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a and the Cardiomyopathy of Senescence: SALT PNUTS, SALT PNUTS!

Abstract: The search for eternal youth is as old as mankind. In a recent Nature paper, Boon et al find that miR34 and its mRNA target PNUTS mediate DNA damage repair and provoke cardiac senescence. Interrupting the miR-34a/PNUTS pathway promises to favorably modify age- and stress-induced cardiac degeneration[AG1] (Boon et al., 2013). “Middle age ends and senescence begins, the day your descendants outnumber your friends.” Ogden Nash. “It’s not the years, Honey, it’s the mileage.” Indiana Jones from Raiders of the Lost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…miRs have emerged as a new class of modulators of gene expression. Among these, miR-34a has been implicated in cardiac-associated damage, particularly cardiac senescence (31). Researchers recently demonstrated that miR-34a was involved in modulating radiation-induced senescence, and that radiation-induced senescence was correlated with the upregulation of miR-34a expression (32).…”
Section: Discussionmentioning
confidence: 99%
“…miRs have emerged as a new class of modulators of gene expression. Among these, miR-34a has been implicated in cardiac-associated damage, particularly cardiac senescence (31). Researchers recently demonstrated that miR-34a was involved in modulating radiation-induced senescence, and that radiation-induced senescence was correlated with the upregulation of miR-34a expression (32).…”
Section: Discussionmentioning
confidence: 99%
“…miR-34a maps to the 1p36 genomic region in humans, and is expressed at higher levels compared to other family members. Several studies have indicated that upregulation of miR-34a can induce apoptosis, senescence, differentiation, cell-cycle arrest, and growth suppression ( 8 10 ). The abnormal expression of miR-34a results in cell-cycle arrest, growth inhibition and attenuated chemoresistance to antitumor drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Human PNUTS (PP1 Nuclear Targeting Protein) is a Protein Phosphatase 1 (PP1) binding protein with critical functions in the response to cellular stresses, including DNA damage, and the regulation of RNA-polymerase II -mediated gene expression [1][2][3][4][5]. It forms a ternary complex with PP1, Tox4 and WDR82 that targets PP1 to the nucleus [3][4][5][6][7][8][9][10], and further interacts with the tumour suppressor phosphatase and tensin homolog PTEN [11].…”
Section: Introductionmentioning
confidence: 99%
“…It forms a ternary complex with PP1, Tox4 and WDR82 that targets PP1 to the nucleus [3][4][5][6][7][8][9][10], and further interacts with the tumour suppressor phosphatase and tensin homolog PTEN [11].…”
Section: Introductionmentioning
confidence: 99%